Lead free solder materials study - Nash Hairie Rosly (Nanyang Technological University, 2020)
The paper aims to examine the creep performance of lead-free solder, SAC387 (95.5Sn-3.8Ag-0.7Cu) at various stress and temperature conditions. Five sets of test results with various stress levels and temperature conditions: (5MPa, 100C), (10MPa, 25C), (10MPa, 75C), (10MPa, 100C) and (15MPa, 100C), were utilised to investigate the creep behaviour of SAC387 solder alloy. Studies were conducted to investigate the trends of creep behaviour for constant stress level with varying temperature conditions and for constant temperature condition with varying stress levels. In both studies, the steady-state creep strain rate depicts an increased with rising temperature conditions and levels of stress, for constant stress level with varying temperature conditions and for constant temperature condition with varying stress levels, respectively. With the test parameters (15MPa, 100C) experiencing the highest steady-state creep strain rate, while the test parameters (5MPa, 100C) possessing the lowest steady-state creep strain rate. Hyperbolic-sine creep model was constructed by employing the steady-state creep strain rate extracted from experimental test results: (5MPa, 100C), (10MPa, 100C) and (15MPa, 100C). And, was compared to other reported hyperbolic-sine creep models. With reference to the other reported creep models by Pang [1], Lau [2] and Schubert [3], the Author’s hyperbolic-sine creep model complements the other reported models and has considerable semblance with the model reported by Pang [1].